Scientific landscape and visualization analysis of the link between adenomyosis and infertility from 2000 to 2024 - Qiaomei Yang; Qiaomei Yang; Qiaomei Yang; Xinye Zheng; Xinye Zheng; Xinye Zheng; Fuchun Zhong; Li Chen; Li Chen; Li Chen; Jingxuan Hong; Xianhua Liu; et al. (Frontiers in Medicine)
ObjectivesAdenomyosis (AM) is a chronic disorder that significantly impacts women’s health and quality of life worldwide, particularly by causing progressive impairment in fertility. This study aimed to summarize and visualize the literature concerning AM-associated infertility using scientometric analysis.MethodsWe conducted a literature search in the Web of Science™ Core Collection (WoSCC) database for “adenomyosis” and “infertility” as topics from 2000 to 2024. The collected data were organized in Microsoft Office Excel for further analysis. Bibliometric analyses and visualizations were performed using Origin, CiteSpace, VOSviewer, and the Bibliometrix package.ResultsA total of 456 articles were published across 153 journals, reflecting a growing trend in both published and cited articles. The scholars with the highest output were Petraglia F., Chapron C., and Pellicer A., while the Fertility and Sterility were the most publications’ journal. China, the United States, and Italy ranked as the top three countries globally regarding relevant publications worldwide. The 190 keywords in the literature were divided into eight clusters primarily related to pathogenesis, adverse factors affecting pregnancy, treatment methods, diagnostic methods, disease progression, in vitro fertilization (IVF) management, infertility in women, and fertility management. Current hotspots in this field include investigating potential mechanisms of pathogenesis, diagnostic strategies, and improving pregnancy outcomes for patients with AM-associated infertility.ConclusionThis study highlights that infertility is the most significant and complex issue associated with AM. Although chronic disease management strategies, pharmacological treatments, and assisted reproductive technologies (ART) have improved fertility outcomes in women with AM, further clinical translational research is still warranted.